Surgical anatomy of the rectum: Round Table Benign Anorectal Processes; introduction Alberto R. Aguiar - Delgado, Bolívar (Cirugía del Uruguay, 1973)
Regarding the subject, we will insist on some aspects of the surgical anatomy of the rectum: A) concept of the organ; B) sphincter system; C) perirectal e-spaces.